The Sensory Characteristic of Caulerpa Jelly Candy Based on The Consumers Acceptance - Alfonsina Marthina Tapotubun; Th. E. A. A. Matrutty; Elizabeth Julenty Tapotubun; Meigy Nelce Mailoa; Eirene G. Fransina (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2018)
To know sensory characteristic of jelly candy based on consumers acceptances. This research used trial method, with ratio between Caulerpa sp and sugar were 1:0.5, 1:1 and 1:1.5. Result of consumer acceptances tests toward color, taste, texture and odor of Caulerpa jelly candy was collected using hedonic range. Caulerpa seaweed could be processed to be jelly candy with consumer acceptance level in range â€œneutralâ€ to â€œlikeâ€. The highest level of consumer acceptance was on the Caulerpa ratio 1:1.5 with acceptance level for color, odor and texture were â€œnot much likeâ€, meanwhile acceptance level for taste was â€œlikeâ€.